2022
DOI: 10.1002/jppr.1787
|View full text |Cite
|
Sign up to set email alerts
|

Significant predictors for topiramate pharmacokinetics: a systematic review of population pharmacokinetic studies

Abstract: Background: Topiramate (TPM) is a second-generation antiepileptic drug with a good pharmacokinetic profile; nonetheless, several factors such as age, renal function and concomitant medications have been reported to affect TPM clearance and dosage adjustments are necessary. Several population pharmacokinetic studies of TPM were developed and the results were partially inconsistent, with different predictors for TPM pharmacokinetic parameters and different structural models. Thus, we aimed to systematically summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The topiramate V d /F was increased with body weight, where allometric scaling was applied with the exponent of 1. The estimated V d /F was approximately 30% decreased than that of the previous model, but it was a reasonable value compared to the reported V d /F of topiramate 11,12 . The final parameter estimates for CL/F and V d /F were 2.1 ± 0.8 L/h and 82.4 ± 13.3 L for the total samples.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The topiramate V d /F was increased with body weight, where allometric scaling was applied with the exponent of 1. The estimated V d /F was approximately 30% decreased than that of the previous model, but it was a reasonable value compared to the reported V d /F of topiramate 11,12 . The final parameter estimates for CL/F and V d /F were 2.1 ± 0.8 L/h and 82.4 ± 13.3 L for the total samples.…”
Section: Resultssupporting
confidence: 55%
“…The estimated V d /F was approximately 30% decreased than that of the previous model, but it was a reasonable value compared to the reported V d /F of topiramate. 11,12 The final parameter estimates for CL/F and V d /F were 2.1 AE 0.8 L/h and 82.4 AE 13.3 L for the total samples. The estimated level of topiramate showed a consistent pattern with the spot serum level (Table 1).…”
Section: Topiramate Pharmacokineticsmentioning
confidence: 96%
“…The variability of TPM ke and V in the final model (the coefficient of variation was 104% and 54%, respectively) were considerably high but within the range of previously reported interindividual variability estimated directly within the range (23.6%-175.0% for V and 13.9%-65.0%) using the parametric approach. 33 The high variability reported in this study could be explained by the poor documentation that resulted in many missing dosing histories and sampling times. This resulted in a high residual variability with a gamma value of 5.5.…”
Section: Covariate Modelingmentioning
confidence: 83%
“…Findings of this study are consistent with those of a recent systematic review of 10 population PK studies using parametric approaches. 33 The authors found that concomitant medication, weight, age, sex, creatinine clearance, and daily TPM dose were essential predictors of TPM CL. However, they suggested further investigating the effect of TPM dose on CL because only 1 study has reported the effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation